2020
DOI: 10.1177/2042018820958331
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones and modulation of diastolic function: a promising target for heart failure with preserved ejection fraction

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a clinical syndrome with high mortality for which there is no proven therapy to improve its prognosis. Thyroid dysfunction is common in heart failure (HF) and is associated with worse prognosis. In this review, we discuss the cardiovascular effects of thyroid hormones, the pathophysiology of HFpEF, the prognostic impact of thyroid function, and the potential of thyroid hormones for treatment of HFpEF. Thyroid hormones have a central role in cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 94 publications
(159 reference statements)
0
15
0
Order By: Relevance
“…Recent clinical studies have reported that patients with cardiovascular disease who have reduced T3 levels have a higher risk of death from heart failure ( Wang et al, 2017 ; Neves et al, 2019 ). Rezvi et al reviewed thyroid hormone supplementation in HF ( Neves et al, 2020 ). Studies in patients without HF as well as HFrEF suggest an effect of thyroid hormone supplementation in improving diastolic function ( Pingitore et al, 2008 ).…”
Section: Hypothyroidism and The Cardiovascular Systemmentioning
confidence: 99%
“…Recent clinical studies have reported that patients with cardiovascular disease who have reduced T3 levels have a higher risk of death from heart failure ( Wang et al, 2017 ; Neves et al, 2019 ). Rezvi et al reviewed thyroid hormone supplementation in HF ( Neves et al, 2020 ). Studies in patients without HF as well as HFrEF suggest an effect of thyroid hormone supplementation in improving diastolic function ( Pingitore et al, 2008 ).…”
Section: Hypothyroidism and The Cardiovascular Systemmentioning
confidence: 99%
“…Thyroid hormones have a direct and indirect cellular effect on the cardiac-renal-vascular system 8 . Excess T3 causes tachycardia, diminished systemic vascular, increased cardiac preload and ventricular contractility 16 , resulting in increased cardiac output and hypertension 8 . The results of a study in Hong Kong stated that 591 patients with hyperthyroidism, 9% were accompanied by hypertension, and the prevalence of heart failure was higher in patients with hypertension 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormones impact on cardiovascular system and their alterations increase cardiovascular risk through genomic and non-genomic mechanisms (39)(40). A local cardiac hypothyroidism may be present even if plasmatic thyroid hormones are normal due to an upregulation of type 3 iodothyronine deiodinase (40).…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…Thyroid hormones impact on cardiovascular system and their alterations increase cardiovascular risk through genomic and non-genomic mechanisms (39)(40). A local cardiac hypothyroidism may be present even if plasmatic thyroid hormones are normal due to an upregulation of type 3 iodothyronine deiodinase (40). Both clinical and subclinical hypothyroidism increase risk of HF (41), and data from epidemiological studies described low triiodothyronine (T3) syndrome in about 22% of HFpEF patients and subclinical hypothyroidism in 10 to 20% (29) (42).…”
Section: Thyroid Hormonesmentioning
confidence: 99%